The Effect Of Prenatal Exercise Toward Clinical Outcome On Delivery Process At Permata Bunda Clinic, Serang In 2018 - Putri, Nazwita Dewi; Shinta Novelia; Uswatun Khasanah; Tommy J Wowor (Rajaki of Tulip Medika Publisher, 2024)
Prenatal exercise is one of activities in services during pregnancy. Prenatal exercise result in a better pregnancy product and better delivery outcome, compared to the mothers that do not follow prenatal exercise. Delivery is a physiological process. If the mother gets no clear information and do not examine her pregnancy regularly, it becomes pathological. The research aims to determine the effect of prenatal exercise toward clinical outcome in the delivery process at Permata Bunda clinic Serang 2018. The method used in the research was quasi Experimentt control group design. The samples were 20 pregnant mothers who follow prenatal exercise at Permata Bunda Clinic Serang. The result shows that prenatal exercise affect clinical outcome during the delivery process phase I,II,III,IV which is significant among experiment group (p = 0,000). Prenatal exercise could decrease pain and accelerate labor process. Permata Bunda Clinic needs to socialize the prenatal exercise program regularly.